PERAN GURU DALAM MENGOPTIMALKAN KEMANDIRIAN ANAK USIA 4-5 TAHUN DI TK ISLAM NUSANTARA - Pinka Citra Amanda; Cucu Atikah; Tricahyani Endah Yuniarti (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2019)
Independence in children must be stimulated early because independent children cannot influence other developments, as well as the independence of children cannot be independently independent without the role of the teacher who helps independence in children. This study aims to determine the role of teachers in optimizing the independence 4-5 years old children at TK Islam Nusantara kota Serang, Banten. This research method uses qualitative methods carried out on 4-5 years old children in group A with a total of 11 children consisting of 7 boys and 4 girls. Procedure for data collection is done by observation, field notes, interviews and documentation. Data analysis using data reduction, data presentation, and conclusions. From the results of the study, that the independence of children aged 4-5 years in group A is good. this is seen when children can adjust to a school environment without parents, children can share, children can interact with friends, children do things on their own initiative, children can solve problems children can be patient in the queue, children can wash their own hands, children can open drinking bottles and eat in their own place, children can eat and drink by themselves, children can use adhesive shoes, children children's children can complete assignments from the teacher, children dare to say what they want, children have high curiosity, children admit mistakes that have been made, children are able to be responsible for themselves. And for the role of the teacher as a motivator, mentor, and inspirator where the role of the teacher is very helpful for the child to implement independence in daily life.